Rancang Bangun Aplikasi Pembelian Voucher Wifi dengan Payment Gateway dan Radius - Indra Gunawan, Gun Gun; Antonius Alijoyo, Franciskus (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
The RT/RW Net business is a promising business opportunity in the digital era, this business provides easy and cheap internet access for the community. However, currently the voucher purchase transaction process is quite complicated. Customers or resellers must come to the sales location, problems occur when RT/RW Net business actors are busy. This causes RT/RW Net business actors to not have time to print WiFi vouchers and carry out WiFi voucher sales transactions. This causes a decrease in sales turnover. The traditional voucher purchasing system through printing vouchers is considered ineffective and inefficient. This research aims to make it easier for customers or resellers to purchase wifi vouchers. The application development process uses the Waterfall method. Android application uses Kotlin, web management application uses Laravel, Payment Gateway uses Xendit, and user management uses Radius. The results of this application make it possible to purchase Wifi vouchers easily and quickly via smartphone. Users can choose a voucher, payment method, and get a voucher code to enter the wifi Network.